1993
DOI: 10.1111/j.1365-2052.1993.tb00352.x
|View full text |Cite
|
Sign up to set email alerts
|

Biochemical characterization of the feline AB blood group system

Abstract: SummaryThe biochemical nature of the feline AB blood group system was characterized by analysing red blood cells from homozygous (genotype A/A) and heterozygous (A/B) type A, type B (B/B), and type AB cats. High performance thin layer chromatography (HPTLC) of red cell gly‐colipids revealed that specific neuraminic acids (NA) on gangliosides, containing ceramide dihexoside (CDH) as a backbone, correlated with the feline AB blood group antigens. Although disialogangliosides predominated, mono‐ and trisialogangl… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
48
0
2

Year Published

2004
2004
2022
2022

Publication Types

Select...
4
2

Relationship

0
6

Authors

Journals

citations
Cited by 50 publications
(73 citation statements)
references
References 22 publications
1
48
0
2
Order By: Relevance
“…The common types are allelic, with type A dominant to type B. A rare type AB, which shows agglutination with both anti-A and anti-B, has not been as clearly defined, but is suspected to be allelic to types A and B [6,7]. Several studies have shown familial segregation for cat blood types A and B.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…The common types are allelic, with type A dominant to type B. A rare type AB, which shows agglutination with both anti-A and anti-B, has not been as clearly defined, but is suspected to be allelic to types A and B [6,7]. Several studies have shown familial segregation for cat blood types A and B.…”
Section: Introductionmentioning
confidence: 99%
“…However, families segregating for type AB are limited and the parentage of the matings was not confirmed. Therefore, the inheritance of the third type AB allele was not clearly resolved [6,7], although it appears to be recessive to type A and dominant to type B [8]. …”
Section: Introductionmentioning
confidence: 99%
“…15,16 Feline blood type A or B is determined by the pres ence of certain RBC membrane glycolipids; type AB contains a mixture of both types. [17][18][19][20] Unlike dogs, by 1-2 months of age, cats produce alloantibodies against RBC antigens they lack without prior sensitization from a blood transfusion. 21 Because blood transfusion is not required for the production of these antibodies, they are referred to as "naturally occurring" alloantibodies.…”
Section: Feline Blood Typesmentioning
confidence: 99%
“…Necessary reagents for the slide test include serum from a type B cat, used as the antiA solution, and a prepared solution of Triticum vulgaris lectin (Sigma Chemical Co., Product L9640, St. Louis, MO), used as the antiB solution. 17,19,27 Triticum vulgaris, a wheat germ lectin, when prepared at a specific concentration, pref erentially causes agglutination of type B feline RBCs. A stock solution is prepared: 25 mg of lyophilized Triticum vulgaris lectin powder is resuspended in 12.5 mL of 0.9% saline and kept frozen.…”
Section: Ab Blood Typingmentioning
confidence: 99%
See 1 more Smart Citation